2017
DOI: 10.3126/mjsbh.v16i1.16986
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ureterolithotomy: A Prospective Comparative Study

Abstract: Introduction: With the developments of non invasive and minimally invasive technology in the management of urolithiasis, the choice of open surgery is rapidly decreasing. The optimal modality of stone management is governed by multiple factors like stone parameters, patient character, availability of technology and surgeon's skill. Open or laparoscopic ureterolithotomy can be used as primary treatment option for large, impacted ureteral stones of more than 1.5 cm or as an adjunct procedure in case of failed ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Wani and Durrani's study [10] also stated that all cases of ureteral stones treated with a laparoscopic retroperitoneal procedure were successful. After three months of follow-up, CT urography results of all patients showed that the ureters were within normal limits, so a stone-free rate of 100% could be stated [8], [10], [12]. This study also found that the success rate of the laparoscopic procedure was 94.1%.…”
Section: Suyadnya Kurniawansupporting
confidence: 56%
See 4 more Smart Citations
“…Wani and Durrani's study [10] also stated that all cases of ureteral stones treated with a laparoscopic retroperitoneal procedure were successful. After three months of follow-up, CT urography results of all patients showed that the ureters were within normal limits, so a stone-free rate of 100% could be stated [8], [10], [12]. This study also found that the success rate of the laparoscopic procedure was 94.1%.…”
Section: Suyadnya Kurniawansupporting
confidence: 56%
“…The demographic data shows that the mean age of the sample is 44.19 ± 11.8 years (transperitoneal laparoscopic ureterolithotomy) and 40.05 ± 12.2 years (open ureterolithotomy), with men still dominating, namely 18/3 patients (trans-peritoneal laparoscopic ureterolithotomy) and 13/8 patients (open ureterolithotomy). Stone size in this study was a mean of 17 ± 5 mm in the trans-peritoneal laparoscopic ureterolithotomy group and 15 ± 5.2 mm in the open ureterolithotomy [8].…”
Section: Suyadnya Kurniawanmentioning
confidence: 58%
See 3 more Smart Citations